2018
DOI: 10.1021/acs.jpca.8b04713
|View full text |Cite
|
Sign up to set email alerts
|

Direct versus Indirect Photodissociation of Isoxazole from Product Branching: A Chirped-Pulse Fourier Transform mm-Wave Spectroscopy/Pulsed Uniform Flow Investigation

Abstract: The UV photodissociation of isoxazole (c-CHNO) is studied in this work by chirped-pulse Fourier transform mm-wave spectroscopy in a pulsed uniform Laval flow. This approach offers a number of advantages over traditional spectroscopic detection methods due to its broadband, sub-MHz resolution, and fast-acquisition capabilities. In coupling this technique with a quasi-uniform Laval flow, we are able to obtain product branching fractions in the 193 nm photodissociation of isoxazole. Five dissociation channels are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 55 publications
5
30
0
Order By: Relevance
“…The key role of the singlet vinylnitrenes production in the low energy photoreactions of isoxazole was additionally confirmed [25]. The most recent experimental investigation on the fragmentation pathways of isoxazole was performed by Dias et al [24], who observed photodissociation in the UV using a chirped-pulse Fourier transform mm-wave spectroscopy in a pulsed uniform flow. Upon irradiation at 193 nm (6.42 eV), HCN and CH3CO were the predominant dissociation products detected with the branching ratios 53.8 and 23.4%, respectively [24].…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…The key role of the singlet vinylnitrenes production in the low energy photoreactions of isoxazole was additionally confirmed [25]. The most recent experimental investigation on the fragmentation pathways of isoxazole was performed by Dias et al [24], who observed photodissociation in the UV using a chirped-pulse Fourier transform mm-wave spectroscopy in a pulsed uniform flow. Upon irradiation at 193 nm (6.42 eV), HCN and CH3CO were the predominant dissociation products detected with the branching ratios 53.8 and 23.4%, respectively [24].…”
mentioning
confidence: 86%
“…The calculations performed by Bouchoux et al [14] showed that ionization of isoxazole involves isomerization of the parent cation and proceeds through ring-opening by cleavage of the N-O bond. This is also an established initial step for neutral isoxazole dissociation [17], [18], [19], [20], [22], [23], [24], [25], [27].…”
Section: Appearance Energiesmentioning
confidence: 99%
See 3 more Smart Citations